Gene-Expression Analysis Identifies IGFBP2 Dysregulation in Dental Pulp Cells From Human Cleidocranial Dysplasia - Greene, Stephen L.; Mamaeva, Olga; Crossman, David K.; Lu, Changming; MacDougall, Mary (Frontiers in Genetics, 2018)
Cleidocranial dysplasia (CCD) is an autosomal dominant disorder affecting osteoblast differentiation, chondrocyte maturation, skeletal morphogenesis and tooth formation. Dental phenotype in CCD include over-retained primary teeth, failed eruption of permanent teeth and supernumerary teeth. The underlying mechanism is unclear. We previously reported one CCD patient with allelic RUNX2 deletion (CCD-011). In current study, we determined the transcriptomic profiles of dental pulp cells from this patient compared to one Sex-and-age matched non-affected individual. Next Generation RNA sequencing revealed that 60 genes were significantly dysregulated (63% upregulated and 27% downregulated). Among them, IGFBP2 (insulin-like growth factor binding protein-2) was found to be upregulated more than two fold in comparison to control cells. Stable overexpression of RUNX2 in CCD-011 pulp cells resulted in the reduction of IGFBP2. Moreover, ALPL expression was up-regulated in CCD-011 pulp cells after introduction of normal RUNX2. Promoter analysis revealed that there are four proximal putative RUNX2 binding sites in -1.5kb IGFBP2 promoter region. Relative luciferase assay confirmed that IGFBP2 is a direct target of RUNX2. Immunohistochemistry demonstrated that IGFBP2 was expressed in odontoblasts but not ameloblasts. This report demonstrated the importance of RUNX2 in the regulation of gene profile related to dental pulp cells and provided novel insight of RUNX2 into the negative regulation of IGFBP2.